Management Information Systems: Characteristics, Applications, and Future Technological Developments - Mansur Chadi Mursid; Rina Tri Astuti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Management Information Systems (MIS) play a crucial role in information management and decision-making processes in an organization. This study aims to identify the main characteristics of MIS, factors that influence its implementation, and the benefits that organizations can obtain from using this system. The method used is a literature study with a descriptive-critical approach to analyze various academic references related to MIS. The results of the study indicate that MIS can improve operational effectiveness, accelerate access to information, and strengthen organizational competitiveness. However, in its implementation, there are various obstacles such as limited resources, resistance to change, and challenges in data security and integration. Along with the development of technologies such as artificial intelligence (AI), big data, and the Internet of Things (IoT), MIS in the future is predicted to become more complex but more optimal. Therefore, the right implementation strategy and active involvement of stakeholders are the main factors in the success of MIS implementation.